Pengaruh Model Pembelajaran Logan Avenue Problem Solving-Heuristic terhadap Kemampuan Literasi Sains Materi Perubahan Wujud Zat pada Siswa MI - Jihan Ayu Fame Liasari; Surayanah Surayanah (FONDATIA, 2026)
Scientific literacy is an important skill that elementary school students need to master in understanding and solving science-based problems. However, science learning in elementary schools is still not optimal because students experience difficulties in understanding concepts, solving problems step by step, connecting material with everyday life contexts, and have not yet been actively involved in the learning process. This condition affects students’ low scientific literacy, particularly in the material on changes in states of matter. This study aims to prove the effect of the Logan Avenue Problem Solving-Heuristic (LAPS-Heuristic) learning model on students’ scientific literacy. This study employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research participants consisted of an experimental class and a control class selected through the purposive sampling technique. Data were collected through scientific literacy tests and observation guidelines for the implementation of learning. The results show that the implementation of the LAPS-Heuristic learning model was in the very good category, with a percentage of 94% in the first meeting and 97% in the second meeting. The most prominent improvement in students’ scientific literacy occurred at the stage of understanding the problem, which was aligned with the content aspect, namely students’ ability to identify and understand the concept of changes in states of matter based on the phenomena presented. The hypothesis test results using the independent samples t-test showed a significance value of 0.001 < 0.05, indicating a significant difference between the experimental class and the control class. Thus, the LAPS-Heuristic learning model has a positive effect on the scientific literacy of Grade IV MI students. The implications of this study indicate that structured problem-solving-based learning can help students understand problems more meaningfully and contextually, making it suitable as an alternative for science learning in elementary schools.